Jesuit art - Mochizuki, Mia M. (Brill Research Perspectives in Humanities and Social Sciences., 2022)
In 'Jesuit Art', Mia Mochizuki considers the artistic production of the pre-suppression Society of Jesus (1540-1773) from a global perspective. Geographic and medial expansion of the standard corpus changes not only the objects under analysis, it also affects the kinds of queries that arise. Mochizuki draws upon masterpieces and material culture from around the world to assess the signature structural innovations pioneered by Jesuits in the history of the image. When the question of a?Jesuit style? is rehabilitated as an inquiry into sources for a spectrum of works, the Society?s investment in the functional potential of illustrated books reveals the traits that would come to define the modern image as internally networked, technologically defined, and innately subjective. 0Also available in Open Access.